Spectral Imaging Technology - A Review on Skin and Endoscopy Applications - Fawzy, Yasser; Zeng, Haishan (Recent Patents on Medical Imaging (Discontinued), 2014)
Spectral imaging technology is an emerging modality that combines the advantages of both imaging and spectroscopy (high spatial and spectral resolution) in one device. The technology has potential in numerous medical imaging and diagnostic applications. In this review, we describe the techniques used to acquire spectral images and the methods used for analyzing spectral images. We then provide detailed review about the progress of the spectral imaging technology in skin and endoscopy applications. This review also covers the recent patents on spectral imaging devices, methods, and data analysis algorithms.
Keywords: optical absorption